2019
DOI: 10.3390/agronomy9110700
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mineral Phase Associated Soil Organic Matter Composition due to Varying Tillage Intensity

Abstract: The volume of soil organic matter (SOM) changes, owing to variations in tillage systems. Conservation tillage (CT) is a useful method for recovering the SOM content of crop fields. However, little is known about the SOM composition of silt- and clay-associated and aggregate-occluded organic matter (OM). The present study aimed at determining the SOM compositions of various SOM fractions in the same Luvisol in a native forest and under ploughing and CT. SOM fractions (silt and clay associated; sand and aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This could indicate that mulches, especially straw, enhanced more aliphatic compounds in the aggregates. The greater iAR could result from the increase of SOM mineralization, which contained the aggregated-related aliphatic compounds (Jakab et al 2019) and could be related to the proportion of aromatic compounds (lignin, phenols, and alkylaromatics) in the materials (Laudicina et al 2015;Wiedemeier et al 2015). Corvasce et al (2006) reported that the aromatic compounds exist differently according to the plant residues and could be released into the soil through microbial decomposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that mulches, especially straw, enhanced more aliphatic compounds in the aggregates. The greater iAR could result from the increase of SOM mineralization, which contained the aggregated-related aliphatic compounds (Jakab et al 2019) and could be related to the proportion of aromatic compounds (lignin, phenols, and alkylaromatics) in the materials (Laudicina et al 2015;Wiedemeier et al 2015). Corvasce et al (2006) reported that the aromatic compounds exist differently according to the plant residues and could be released into the soil through microbial decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…The aromatic compounds are likely to adsorb onto the soil particles rather than dissolve (Corvasce et al 2006). Moreover, soil disturbance like tillage or soil stirring is expected to increase aromaticity in the aggregates-occluded soil organic matter (Jakab et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another aliquot from the same sample was heated to 900°C, where the total C content was released as CO 2 and measured by the NDIR detector. Total organic carbon (TOC) concentration was then calculated as the difference between total and inorganic carbon content (Jakab et al, 2016(Jakab et al, , 2019. To compare the TOC concentrations of soils with different cultivation and compaction, TOC stocks (t ha −1 ) were calculated using Equation (1):…”
Section: Soil Sampling and Measurementsmentioning
confidence: 99%
“…Soil samples for all the other measurements were dried at 45 • C in a drying oven until the air-dried state. The soil organic carbon (SOC) content was measured using dry combustion at 900 • C [27] using a Shimadzu TOC-L with an SSM 5000A solid sample combustion unit (Shimadzu Corp., Tokyo, Japan). The total bounded nitrogen (TN) content was measured using dry combustion at 860 • C [27] using a Teledyne Tekmar A9000N chemiluminescent analyzer (Teledyne Technologies Incorp., Thousand Oaks, California, USA) with a Rosemount type 183 boat sampling module (Rosemount Inc. Shakopee, Minnesota, USA).…”
Section: Physical and Chemical Analysis Of The Soil Samplesmentioning
confidence: 99%